Closing the “Bergson Gap”: New Data on a Problem in Soviet Statistics - Davies, R. W. (The Review of Economics and Statistics, 2004)
Over fifty years ago, Abram Bergson, Janet Chapman, and others sought to assess the large gap in Soviet statistics between the published wage bill and the full wage bill; and Frank Lorimer drew attention to the related gap between the employment data in the 1939 population census and in the annual employment returns. Soviet archives which have recently been declassified reveal the considerable extent to which the findings of the Western authors were accurate.